The Effect of Volataile Fatty Acid on an Aerobic Biofilm Reactor Using Dairy Wastewater - Sivakumar, M. S.; Asha, B. (Challenging Issues on Environment and Earth Science Vol. 4, 2021)
The use of anaerobic biofilm reactors for the treatment of various effluents has been established in recent decades. The ability to maintain microorganisms acted as a biofilm factor influencing the reactor's performance. The reactor performance is usually evaluated in terms of process efficiency and stability through estimation of organic matter removal, VFA levels, quantity and composition of biogas produced, etc. The purpose of this research is to evaluating the effectiveness of treating a dairy effluent with high pollution potential. The effluent was evaluated with an average value of Volatile Fatty Acid (VFA) of 172.8, 132.0, 193.0, 203.0 and 172 mg/L and an Organic Loading Rate (OLR) of 0.1502, to 0.266 kg COD/ m3/day, w. The maximum COD elimination efficiency of 84% along with production of 0.048m3/kg COD of biogas at 3 days Hydraulic Retention Time (HRT) was noticed.